REMAJA, MEDIA SOSIAL DAN UJARAN KEBENCIAN: STUDI KONSUMSI ONLINE RELIGIOUS CONTENT DI BANTEN - Setianto, Yearry Panji; Nurjuman, Husnan; Handaningtias, Uliviana Restu (Interaksi: Jurnal Ilmu Komunikasi, 2023)
Religious hate speech has become more visible in social media, following high-profile cases such as the Church bombing in Sri Lanka and the Friday Prayer shooting in New Zealand in 2019. This research examines the understanding of youth in Banten, an Indonesian province with low religious tolerance, regarding the circulation and consumption of religious hate speech. Using a case study approach and focus group discussions with 33 youth in Banten who consume religious content online, the researchers found that online/social media are becoming the primary platform for learning about religion, despite the frequent exposure to religious content associated with hate speech, especially in relation to politics. The researchers also found that the presence of opinion leaders (religious teachers, parents) and media literacy are important factors in mitigating the spread of religious hate speech.